Preparation and Characterization of CuONanoparticles Prepared Using Plasma Jet Method - Fadhil Mohammed, Shaimaa; Ahmad Mahmood, Olfat; Ali Lateef, Rudainah (Al-Nahrain Journal of Science, 2025)
In this study, copper oxide nanostructures were created using argon plasma jets. Many methodsincludeX-ray diffraction (XRD),Fourier transform infrared (FTIR), and ultraviolet and visible spectroscopy. The XRD pattern of the prepared CuO NPs, and the peaks obtained from CuO nanoparticles were detected at (2Ѳ= 32.69°, 35.73°, 38.92°, 46.49°, 49.06°, 51.62°, and 53.71°) 58.66°, 61.86°, 66.12°, 66.74°, 68.50°, 72.93°, and 75.40°for levels (110) (111−) (111) (112−) (202−) (112) (020) (202) (113−) (022) (311−) (220) (311) (004). These obtained peaks correspond to the crystal structure monoclinic type with lattice constants (a = 4.6350, b = 3.4100, and c = 5.1080 A°), space group (C 12/C 1 no. 15), and crystalline angles (α= γ= 90ᵒ, β= 99.48ᵒ) that closely matched the standard data (JCPDS 96-101-1149). The obtained XRD results of prepared CuO nanoparticles confirmed that the typical crystalline size of CuO nanoparticles is about(24.36 nm).FTIR spectrum showed the main vibration characteristic peaks at 424, 574, 1635, 2352 and 3268 −1of the synthesized CuO NPs. The obtained broad bands referred tothe structures of copper oxides consistingof nanocrystals. The detected CuO nanostructures' UV-Vis findings showed a widepeak of absorptionwithin the wavelengthextendingfrom300cm-1to 400 cm-1, and calculated band gapenergy equal to(1.4 eV).